One-Stage Transperineal Repair of Pan-Urethral Stricture With Dorsally Placed Buccal Mucosal Grafts: Results, Complications, and Surgical Technique - Tavakkoli Tabassi, Kamyar; Mansourian, Ehsan; Yarmohamadi, Aliasghar (Urology Journal, 2011)
Purpose: To report the surgical details and results of one-stage transperineal urethroplasty using dorsal buccal mucosal graft (BMG) in treatment of panurethral stricture. Materials and Methods: This cohort study was carried out on 17 men with pan-urethral stricture who underwent one-stage transperineal BMG urethroplasty. Failure was defined as a need to any intervention during the follow-up period. Results: The etiology of stricture was trauma in 4 (23.5%), sexually transmitted diseases in 4 (23.5%), lichen sclerosus in 2 (11.8%), and idiopathic in 7 (41.1%) patients. The mean follow-up period was 8.5 months (range, 3 to 18 months). Six (35.3%) patients developed complications; namely wound infection in 2 (11.8%), meatal stenosis in 1 (5.9%), and re-stenosis in 3 (17.6%) subjects. Complication rate in patients ≤ 43 and > 43 years old was 25% (2/8) and 44% (4/9), respectively, which did not reach statistically significant difference (P = .6). The final success rate was 88.2%. None of the patients needed open redo-urethroplasty during the follow-up period. Conclusion: Reconstruction of pan-urethral strictures may be safely and effectively performed at a simple single operative procedure using a transperineal approach with combinations of dorsal BMG.